Knowledge and Compliance With Standard Precautions Among Nurses - Fares Ghabayen RN, MSN; Mohammed ALBashtawy PhD; Raghad Hussein Abdelkader PhD; Samiha Jarrah PhD; Nidal Eshah PhD; Asem Abdalrahim PhD; Ahmad Saifan PhD; Abdullah Alkhawaldeh PhD; Ahmad Rayan PhD; Ahmad Ayed PhD, MSN, RN; Rasmieh Al-Amer PhD; Khitam Ibrahem Mohammad PhD, MSN, RN; et al. (SAGE Publishing, 2023)
Introduction The spread of microorganisms is caused by direct or indirect contact, respiratory droplets, and airborne transmission. Knowledge and compliance with standard precautions are crucial in preventing infection in the hospital. Objectives To assess the level of knowledge and compliance with standard precautions among registered nurses who work in military hospitals and the factors affecting compliance with standard precautions. Methods A descriptive cross-sectional study was conducted. Four hundred and eight registered nurses at three Jordanian Royal Medical Services hospitals completed an online self-report questionnaire using a convenience sampling technique. The statistical package for social sciences (SPSS) version 25 was used to analyze the data. Results The level of knowledge of standard precautions among nurses was excellent, with an overall mean score of 15.59 ± 2.22 out of 20; around half (54%) of them had an excellent level. Nurses' compliance with standard precautions was intermediate, with an overall mean score of 59.65 ± 14.57 out of 80. Forty-seven percent of nurses had a high degree of compliance. Compliance with standard precautions was correlated positively with age, working experience in years, total knowledge score, training in standard precautions, and availability of personal protective equipment, and negatively with exposure to sharp injuries. Conclusion Nurses play a key role in preventing and managing hospital infections through their responsibility for a large proportion of patient treatment and care. Therefore, efforts should be made to improve nurses' perceptions of the basic elements of standard precautions. Even so, results showed that compliance with standard precautions was intermediate. This highlights the need to take the necessary measures to raise the level of compliance. Even so, results showed that compliance with standard precautions was intermediate. This highlights the need to take the necessary measures to raise the level of compliance.